Frankenstein or a Submarine Alkaline Vent: Who is Responsible for Abiogenesis?: Part 2: As life is now, so it must have been in the beginning. (4th July 2018) - Branscomb, Elbert; Russell, Michael J.
Abstract : We argued in Part 1 of this series that because all living systems are extremely far‐from‐equilibrium dynamic confections of matter, they must necessarily be driven to that state by the conversion of chemically specific external disequilibria into specific internal disequilibria. Such conversions require task‐specific macromolecular engines. We here argue that the same is not only true of life at its emergence; it is the enabling cause of that emergence; although here the external driving disequilibria, and the conversion engines needed must have been abiotic. We argue further that the initial step in life's emergence can only create an extremely simple non‐equilibrium "seed" from which all the complexity of life must then develop. We assert that this complexity develops incrementally and progressively, each step tested for value added "in flight." And we make the case that only the submarine alkaline hydrothermal vent (AHV) model has the potential to satisfy these requirements. Abstract : The redox‐active ferrous/ferric mineral, green rust —precipitated at the interface of alkaline hydrothermal springs and the carbonic Hadean 4.4 billion years ago—was, we contend, the initial seed of all life. In this case it acts as a precursor nitrate/nitrite reductase, delivering ammonia on‐site as aminator at life's hydrothermal hatchery.